Influence Price, Production Rubber and Income on The Level of Welfare of Rubber Farmers in The Village Ranto Jior District River Right Regency Port Rock South (Jurnal Manajemen Bisnis, 2024)
ABSTRACTThis research aims to determine the impact of price, rubber production, and income on the welfare level of rubber farmers in Ranto Jior Village, Sungai Kana District, South Labuhan Batu Regency. Using a quantitative method with multiple linear regression analysis supported by SPSS version 23, data were collected through questionnaires. The study's population was the residents of Ranto Jior Village, with a sample size of 100 people selected using probability sampling based on the Lemeshow formula. The findings reveal that the welfare of rubber farmers is significantly and positively influenced by rubber prices, rubber production, and income. All three factors—price, rubber production, and income—together significantly influence the welfare of rubber farmers in Ranto Jior Village. The determination test shows that these factors account for 92.8% of the variance in welfare, indicating a very strong influence.